2018
DOI: 10.1111/iep.12289
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxymethylnitrofurazone treatment in indeterminate form of chronic Chagas disease: Reduced intensity of tissue parasitism and inflammation—A histopathological study

Abstract: Summary Hydroxymethylnitrofurazone (NFOH) is a nitrofurazone prodrug effective in vivo during acute infections, and it has less hepatotoxicity effect than the standard drug benznidazole (BZN) which has been used during short‐ and long‐term treatment. In the present study, we induced the indeterminate form of Chagas disease in mice with a Y strain of Trypanosoma cruzi and analysed the histopathological data about the effects of NFOH and BZN on different tissues, including the heart, skeletal muscle, liver, kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 74 publications
2
20
0
1
Order By: Relevance
“…Hydroxymethylnitrofurazone (NFOH-a nitrofurazone derivative) is non-mutagenic in the Ames test [24], non-genotoxic in micronuclei [25], and pharmacokinetic studies in rats [26] and rabbits [27] have shown an increased distribution volume compared to its parent compound nitrofurazone. Additionally, when NFOH toxicity was evaluated after 21 and 60 days treatment, there was reduced hepatic inflammation compared to BZN, and no changes in hepatic enzymes such as aspartate aminotransferase and alanine aminotransferase [28,29]. Here, we report a comprehensive assessment of NFOH activity against T. cruzi.…”
Section: Introductionmentioning
confidence: 94%
“…Hydroxymethylnitrofurazone (NFOH-a nitrofurazone derivative) is non-mutagenic in the Ames test [24], non-genotoxic in micronuclei [25], and pharmacokinetic studies in rats [26] and rabbits [27] have shown an increased distribution volume compared to its parent compound nitrofurazone. Additionally, when NFOH toxicity was evaluated after 21 and 60 days treatment, there was reduced hepatic inflammation compared to BZN, and no changes in hepatic enzymes such as aspartate aminotransferase and alanine aminotransferase [28,29]. Here, we report a comprehensive assessment of NFOH activity against T. cruzi.…”
Section: Introductionmentioning
confidence: 94%
“…The association with fluconazole was not effective.Lourenço et al (2018)Amiodarone hydrochloride (Antiarrhythmic) and/orBenznidazole (Antiprotozoal) T. cruzi (Y strain) cultures with drugs.Drugs combination was effective, but without synergism, since similar results were obtained when the drugs were tested individuallyStrauss et al (2018)Clomipramine (Antidepressant, tricyclic)Benznidazole (Antiprotozoal)Mammalian cells,Synergistic activity in vitro against the clinically relevant life-stages of T. cruzi. Significantly diminished the parasitic load in blood and the mortality rateProvidello et al (2018)Ascorbic Acid (Genitourinary Agent)Benznidazole (Antiprotozoal)Swiss miceReduction in parasitemia, in cardiac parasitism and inflammation, and prevention of the hepatic damage.Scarim et al, 2018b, Scarim et al, 2018aHydroxymethylnitrofurazone (a nitrofurazone prodrug)Benznidazole (Antiprotozoal)Balb/c miceAmastigote nests were not found in heart, skeletal muscle, liver, kidney, colon, spleen and brain. The histopathological analysis showed fewer tissue lesions and parasite infiltratesTorrico F et al (2018)E1224 (a water-soluble ravuconazole prodrug)HumanE1224 displayed a transient, suppressive effect on parasite clearance, whereas benznidazole showed early and sustained efficacy until 12 months of follow-up.Guedes-da-Silva et al (2019)Sterol 14α-Demethylase (Inhibitor VFV)Benznidazole (Antiprotozoal)Swiss Webster miceparasitemia suppression and 100% animal survival Coadministration of Bz + VFV (resulted in 106-fold lower blood parasitism as compared to the monotherapy of Bz)De Araújo et al (2019)Imidazole Derivatives and Benznidazole (Antiprotozoal)MRC -5 cells and Primary cardiac cellsPotent and selective activity against T. cruzi Rial et al, 2019Allopurinol (Antigout) and Benznidazole (Antiprotozoal)C57BL/6J and C3H/HeN miceabsence of electrical abnormalities, significant reductions in antibody titres and parasitic loadsMazzeti et al, 2019Allopurinol combined with benzinidazole (Antiprotozoal) or Nifurtimox (Antiprotozoal)Mammalian cell, Swiss mic...…”
Section: Drug Associationmentioning
confidence: 99%
“…Furthermore, the sequential use of BNZ and allopurinol (used in the treatment of gout) was well tolerated in humans, leading to beneficial therapeutic immunological changes during the chronic CD, significant reduction of parasitic loads, absence of electrical abnormalities in the heart, and increased cure rate (Perez-Mazliah et al, 2012; Rial et al, 2018; Mazzeti et al, 2019). Other combinations with BNZ that have shown to be interesting and deserve better investigation are ascorbic acid (Providello et al, 2018), hydroxymethylnitrofurazone (Scarim et al, 2018a,b), and imidazole (De Araújo et al, 2019).…”
Section: Drug Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are only two drugs approved for the treatment of Chagas disease, Nifurtimox and Benznidazole, which are based on the indirect inhibition of DNA, RNA and protein synthesis due to oxidative damage by the releasing of reactive oxygen species, resulting from the reaction of oxygen with unstable nitroanion metabolites, leading to the inactivation of enzymes and destruction of the parasite [ 63 ]. Although the mechanism of both drugs is not completely elucidated, it should be considered that both are highly hepatotoxic and genotoxic; additionally, these drugs are only highly effective in patients during the acute phase; as the disease progresses towards chronicity, their effectiveness decreases drastically [ 64 , 65 ]. Due to the damage derived from treatments with these drugs, it is necessary to consider the possible interactions that may exist with current COVID-19 treatments and the potential health effects in infected patients.…”
Section: Influence Of Covid-19 Treatment In Patients With Chagas Diseasementioning
confidence: 99%